Meetinghouse Tragedy : An Episode in the Life of a New England Town - Clark, Charles E., 1929- (Book collections on Project MUSE., 1998)
His Meetinghouse Tragedy offers a fascinating glimpse into architectural history, popular and folk culture, religious traditions, and the ways communal memories are formed and then endure.